2022
DOI: 10.1007/s10734-021-00797-2
|View full text |Cite
|
Sign up to set email alerts
|

Mastering humanitarianism? A survey of postgraduate humanitarian courses

Abstract: Humanitarian events are increasing globally, both in number and intensity. In response, the international community spends approximately US$30 billion annually to alleviate both the immediate consequences of these climatic, geographic, and human-induced events but also to support mitigation and recovery. Over the past two decades, the humanitarian sector has increasingly professionalised. One under-studied aspect of this professionalisation is an increase in postgraduate studies in humanitarian action over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…A recent review of humanitarian studies programmes found that the vast majority of them are based in the Global North. Only three out of 26 courses taught in English were offered in the Global South (two in Nigeria, one in India) whereas the rest was offered in the United States, Europe, the United Kingdom, and Australia (Stibral et al, 2022). Based on the comparison of these programmes, the authors of this study observe a lack of agreement on a core curriculum or pedagogy and suggest that stakeholders should be involved in the conceptualisation of a core curriculum.…”
Section: Methods and Knowledge Production In And For Humanitarianismmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent review of humanitarian studies programmes found that the vast majority of them are based in the Global North. Only three out of 26 courses taught in English were offered in the Global South (two in Nigeria, one in India) whereas the rest was offered in the United States, Europe, the United Kingdom, and Australia (Stibral et al, 2022). Based on the comparison of these programmes, the authors of this study observe a lack of agreement on a core curriculum or pedagogy and suggest that stakeholders should be involved in the conceptualisation of a core curriculum.…”
Section: Methods and Knowledge Production In And For Humanitarianismmentioning
confidence: 94%
“…Based on the comparison of these programmes, the authors of this study observe a lack of agreement on a core curriculum or pedagogy and suggest that stakeholders should be involved in the conceptualisation of a core curriculum. Stibral et al (2022) also suggest that 'the critical examination of humanitarian aid and critique of the sector also seem to be only an emerging impetus' (p. 757). However, it is not quite clear whether such an assessment is possible on the basis of course descriptions and it does not reflect the observations of one of the authors of this chapter, who audited and reviewed courses at three of the universities listed in this sample.…”
Section: Methods and Knowledge Production In And For Humanitarianismmentioning
confidence: 99%
“…The humanitarian sector has grown enormously over the past two decades, and some studies reflect (only those in the English language) an increase over the last 20 years in postgraduate studies in humanitarian action, called Masters of Humanitarian Assistance (MHA) that offers differences in coverage, but there is no agreement on core curriculum or pedagogy across humanitarian studies courses [17].…”
Section: The Health Humanitarian Action Master Degreementioning
confidence: 99%
“…As other authors have proposed, there is no agreement on core curriculum or pedagogy across humanitarian studies courses or consensus on what it means to hold a Master's in this field, so it is necessary to provide students of the health professions with tools of this type, training them in theoretical-practical content on global health problems, migratory movements, history, geopolitics, rights, security, health care in vulnerable populations, specific health plans for performance, etc. [17].…”
Section: Introductionmentioning
confidence: 99%